Found - Yoon, Salina (New York : Walker Books for Young Readers, an imprint of Bloomsbury, 2014)
Upon finding a toy rabbit in the forest, Bear tries his very best to return it to its home but by the time its owner appears, Bear has become attached to Bunny.
Keywords: Toys -- Pictorial works -- Juvenile fiction; Bears -- Pictorial works -- Juvenile fiction; Moose -- Pictorial works -- Juvenile fiction; Lost articles -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works; Toys -- Juvenile fiction; Bears -- Juvenile fiction; Moose -- Juvenile fiction; Lost articles -- Juvenile fiction; Children's stories; Lost and found possessions -- Fiction; Toys -- Fiction; Bears -- Fiction; Moose -- Fiction; JUVENILE FICTION -- Social Issues -- Emotions & Feelings; JUVENILE FICTION -- Social Issues -- Friendship; Bears; Children's stories; Lost articles; Moose; Toys; Fiction; Juvenile works; Pictorial works